Contribuições da Filosofia de Giorgio Agamben à Leitura do Caso Justransicional Colombiano - Fernando Cardoso; Jessyca Iasmim de Souza (Araucaria)
The present research problematizes the conception of state of exception proposed by Giorgio Agamben and its perpetuation in the present democracies, from the reading of the conflict existing in Colombia. In order to do so, the objective was to understand the contributions of Giorgio Agamben’s philosophy to the reading of the Colombian justransicional case. From the concepts of state of exception, biopower, force and transitional justice, it is reflected in how the Colombian case leads to a new conception of the state of exception and the justransional framework. Through reflections built on Agamben’s philosophy, it is believed that the Colombian legal-political context perpetuates markers of totalitarianism based on norms and on the relationship between rulers and governed. The existence of aspects related to political- constitutional instability directly interferes with the way in which the State acts in relation to the dialogue with its people and, in the Colombian case, makes it impossible to affirm a full juridical framework. Post-conflict, within the Colombian justransicional framework, needs to reflect the deconstruction of totalitarian aspects maintained in the legal framework, especially with regard to the overcoming of the colonization marks in the process of constitutional formation of the country.